EFFECT OF SALINITY ON GROWTH AND PROTEIN CONTENT OF RICE GENOTYPES - Billah, K. M. Masum; Hasan, M. M. Mehedi; Jharna, Dr. Dilruba Easmin (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Rice, the highest producing cereal crops in Bangladesh. Saline induced changes in growth was screened at germination to find out the salt tolerant traditional rice genotypes and chemical tests were carried out to detect the protein-content of rice genotypes. Four traditional rice genotypes (Kalijira, Sakkor khana, Chinigura, Ghoto balam) with one improved variety BRRI dhan28 were used in this experiment. The germination experiment was conducted in petri dish at 0, 8, 12, 16 dS/m salinity with three replications each. Based on the data obtained, the genotypes were scored and categorized as highly tolerant (score 1), tolerant (score 3), moderately tolerant (score 5), susceptible (score 7), and highly susceptible (score 9) to salinity. Salinity caused reduction in germination and declines of shoot length, root length, shoot wet weight and shoot dry weight. Mean salinity tolerance score (MSTS) was computed. Based on MSTS, two genotypes named Kalijira and Chinigura were selected as tolerant, two genotypes named Sakkor khana and BRRI dhan28 as susceptible, and the rest one genotype named Ghoto balam as highly susceptible to salinity in germination stage. Total protein content of rice genotypes were determined by Kjeldahl method. Among 5 varieties studied, Chinigura contains the highest amount of protein (8.855%). The overall data estimated that, Chinigura is more salt tolerant and highly protein rich genotype than other rice genotypes.